LEXICAL CHANGES AN EXAMPLE OF HARRY POTTER AND HALF-BLOOD PRINCE - Inog’omjonova Robiya Rustamjon qizi (Лучшие интеллектуальные исследования, 2023)
Throughout this article, you will look at several examples of lexical transformations. In addition, you will also get acquainted with a brief description of several sections that belong to the type of lexical transformation. Below are some examples of the type of lexical change provides a better understanding.